Thematic Quranic Interpretation and Islamic Educational Psychology in Explaining Digital anxiety: An Integrative Review - Illah, Moh. Sulthon Aulia; Kahar, Abd.; Syukkur, Abdul (STAI Syaichona Moh. Cholil Bangkalan, 2024)
This study bridges a gap in the integration of Islamic exegesis and contemporary psychological frameworks regarding digital age anxieties feelings of anxiety over potentially missing information, trends, or experiences that others are having. This study employs qualitative techniques, incorporating a literature review that investigates both classical and modern commentaries along with literature on Islamic psychology. The findings suggest that these passages embody spiritual principles that may alleviate Fear of Missing Out, including recognition of the world's impermanence, the significance of self-acceptance, and confidence in and contentment with God's provisions. The main cause of syndrome is an irrational fear (intense anxiety) regarding the information acquired, frequently resulting in feelings of discontent and diminished self-worth.